2023
DOI: 10.1186/s13731-023-00289-w
|View full text |Cite
|
Sign up to set email alerts
|

Socio-economic factors affecting women’s entrepreneurial performance in MSEs in Bahir Dar City, Ethiopia

Abstract: Women’s entrepreneurship is the pillar of economic expansion in many developing countries and is increasingly recognized as an essential driver of economic growth, productivity, innovation, employment, and economic dynamism. This study aimed to investigate the socio-economic factors that affect women’s entrepreneurial performance in MSEs in Bahir Dar City, Ethiopia. This study employed explanatory and descriptive survey designs using a quantitative research approach. The data were gathered from a survey of 348… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 34 publications
(65 reference statements)
0
0
0
Order By: Relevance
“…The study found that the entrepreneurs' entrepreneurial performance was positively influenced by their entrepreneurial competences, their education level, their business experience, and their participation in business networks. Ayinaddis (2023) investigated the socio-economic factors affecting women's entrepreneurial performance in micro and small enterprises (MSEs) in Bahir Dar City, Ethiopia. A quantitative research approach was used, and data was collected from 120 women entrepreneurs through a structured questionnaire.…”
Section: Empirical Reviewmentioning
confidence: 99%
“…The study found that the entrepreneurs' entrepreneurial performance was positively influenced by their entrepreneurial competences, their education level, their business experience, and their participation in business networks. Ayinaddis (2023) investigated the socio-economic factors affecting women's entrepreneurial performance in micro and small enterprises (MSEs) in Bahir Dar City, Ethiopia. A quantitative research approach was used, and data was collected from 120 women entrepreneurs through a structured questionnaire.…”
Section: Empirical Reviewmentioning
confidence: 99%